Resource utilisation and costs in predementia and dementia: a systematic review protocol. Issue 1 (23rd January 2018) - Landeiro, Filipa; Wace, Helena; Ghinai, Isaac; Nye, Elsbeth; Mughal, Seher; Walsh, Katie; Roberts, Nia; Lecomte, Pascal; Wittenberg, Raphael; Wolstenholme, Jane; Handels, Ron; Roncancio-Diaz, Emilse; et al.
Abstract : Introduction: Dementia is the fastest growing major cause of disability globally with a mounting social and financial impact for patients and their families but also to health and social care systems. This review aims to systematically synthesise evidence on the utilisation of resources and costs incurred by patients and their caregivers and by health and social care services across the full spectrum of dementia, from its preceding preclinical stage to end of life. The main drivers of resources used and costs will also be identified. Methods and analysis: A systematic literature review was conducted in MEDLINE, EMBASE, CDSR, CENTRAL, DARE, EconLit, CEA Registry, TRIP, NHS EED, SCI, RePEc and OpenGrey between January 2000 and beginning of May 2017. Two reviewers will independently assess each study for inclusion and disagreements will be resolved by a third reviewer. Data will be extracted using a predefined data extraction form following best practice. Study quality will be assessed with the Effective Public Health Practice Project quality assessment tool. The reporting of costing methodology will be assessed using the British Medical Journal checklist. A narrative synthesis of all studies will be presented for resources used and costs incurred, by level of disease severity when available. If feasible, the data will be synthesised using appropriate statistical techniques. Ethics and dissemination: Included articles will be reviewed for an ethics statement. The findings of the review will be disseminated in a related peer-reviewed journal and presented at conferences. They will also contribute to the work developed in the Real World Outcomes across the Alzheimer's disease spectrum for better care: multi-modal data access platform (ROADMAP). Trial registration number: CRD42017071413 .